2018
DOI: 10.1111/jcmm.13926
|View full text |Cite
|
Sign up to set email alerts
|

γ‐secretase inhibitor DAPT mitigates cisplatin‐induced acute kidney injury by suppressing Notch1 signaling

Abstract: Organ toxicity, including kidney injury, limits the use of cisplatin for the treatment of multiple human cancers. Hence, interventions to alleviate cisplatin‐induced nephropathy are of benefit to cancer patients. Recent studies have demonstrated that pharmacological inhibition of the Notch signaling pathway enhances cisplatin efficacy against several cancer cells. However, whether augmentation of the anti‐cancer effect of cisplatin by Notch inhibition comes at the cost of increased kidney injury is unclear. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…The latter are vital for both membrane structure maintenance and overall mitochondrial activity. As cisplatin levels increase, Bcl-2 is downregulated in response to p53 activation [87,88,89,90].…”
Section: Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%
“…The latter are vital for both membrane structure maintenance and overall mitochondrial activity. As cisplatin levels increase, Bcl-2 is downregulated in response to p53 activation [87,88,89,90].…”
Section: Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%
“…Bcl family proteins are essential for maintenance of mitochondrial function and membrane integrity. There is a strong consensus that the anti-apoptotic mitochondrial protein, Bcl-2, is downregulated in response to cisplatin [40,44,70,75,76,78,79,83,84,88,89,104,105,106,107,108,109,110,111,112,113,114,115,116,117] through p53 activation [111,113,118]. One study, however, showed that Bcl-2 mRNA is increased after administration of cisplatin [119].…”
Section: Introductionmentioning
confidence: 99%
“…DAPT is a speci c inhibitor of the Notch1 signaling pathway (19). DAPT decreased the enhancement effect of TWEAK on the mRNA expression of pro brotic factors, collagen I, bronectin, and α-SMA, as well as Notch1/Jagged1 molecules in HK2 cells (Fig.…”
Section: Resultsmentioning
confidence: 93%